PENGARUH FLEXIBLE WORK ARRANGEMENT TERHADAP ROLE CONFLICT, ROLE OVERLOAD, REDUCED PERSONAL ACCOMPLISHMENT, JOB SATISFACTION DAN INTENTION TO STAY - RAHMAWATI HANNY YUSTRIANTHE (Jurnal Bisnis dan Akuntansi, 2008)
The objective of this study is to test the effect of flex time and standard time to role conflict, role overload, reduced personal accomplishment, job satisfaction and intention to stay. This study uses 128 accounting educators in Jogjakarta as the respondents. Analysis is conducted using Mancova. The result shows that those accounting educators who work in flex time tend to have lower role overload and reduced personal accomplishment than those who work in standard time. However, this study fails to show that accounting educators who work in flex time tend to have lower role conflict, job satisfaction and intention to stay with the firms.